Yield and nutrient uptake by wheat as influenced by integrated use of manures and fertilizers (Journal of the Bangladesh Agricultural University, 2014)
An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during November 2011 to March 2012 to evaluate the effect of integrated use of manures and fertilizers on the growth, yield and nutrient uptake by wheat. There were six treatments such as T0 (Control), T1 [STB-CF (HYG)], T2 [CD + STB-CF (HYG)], T3 [PM + STB-CF (HYG)], T4 [COM + STB-CF (COM)] and T5 [FP (Farmers practice)]. The experiment was laid out in a Randomized Complete Block Design with four replications. The integrated use of manures and fertilizers significantly influenced the yield attributes as well as grain and straw yields of wheat. The treatment T1 [STB-CF (HYG)] produced the tallest plant of 90.17 cm which was identical with T3 [PM + STB-CF (HYG)] and the lowest value was found in control. The 1000-grain weight followed the similar pattern but the tillers hill-1, spike length and spikelets spike-1 did not follow any definite trend. The treatment T3 [PM + STB-CF (HYG)] produced the highest grain yield of 4362 kg ha-1 (90.4% increase over control) and straw yield of 5492 kg ha-1 (84.79% increase over control). The lowest grain yield (2291 kg ha-1) and straw yield (2972 kg ha-1) were found in T0 (Control). The NPKS uptake by wheat was markedly influenced by combined use of manures and fertilizers and the treatment T3 demonstrated superior performance to other treatments. So the treatment T3 comprising poultry manure in combination with chemical fertilizers on IPNS basis was found to be the best combination of manures and fertilizers for obtaining the maximum yield and quality of wheat at BAU farm. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21242 J. Bangladesh Agril. Univ. 12(1): 73-78, June 2014